Practice makes plasticity: 10-Hz rTMS enhances LTP-like plasticity in musicians and athletes - Kweon, Jamie; Vigne, Megan M.; Jones, Richard N.; Carpenter, Linda L.; Brown, Joshua C. (Frontiers in Neural Circuits, 2023)
Motor skill learning has been linked to functional and structural changes in the brain. Musicians and athletes undergo intensive motor training through the practice of an instrument or sport, and have demonstrated use-dependent plasticity that may be subserved by long-term potentiation (LTP) processes. We know less, however, about whether the brains of musicians and athletes respond to plasticity-inducing interventions, such as repetitive transcranial magnetic stimulation (rTMS), differently than those without extensive motor training. In a pharmaco-rTMS study, we evaluated motor cortex excitability before and after an rTMS protocol in combination with oral administration of D-cycloserine (DCS) or placebo. In a secondary covariate analysis, we compared results between self-identified musicians and athletes (M&As) and non-musician and athletes (non-M&As). Three TMS measures of cortical physiology were used to evaluate plasticity. We found that M&As did not have higher baseline corticomotor excitability. However, a plasticity-inducing protocol (10-Hz rTMS in combination with DCS) strongly facilitated motor-evoked potentials (MEPs) in M&As, but only weakly in non-M&As. Placebo and rTMS produced modest facilitation in both groups. Our findings suggest that motor practice and learning create a neuronal environment more responsive to plasticity-inducing events, including rTMS. These findings may explain one factor contributing to the high interindividual variability found with MEPs. Greater capacity for plasticity holds implications for learning paradigms, such as psychotherapy and rehabilitation, by facilitating LTP-like activation of key networks, including recovery from neurological/mental disorders.